Pengenalan Nilai-Nilai PAK melalui Metode Cerita Menggunakan Media Hand Puppet sebagai Tindakan Preventif terhadap Perilaku Bullying pada Anak Usia Dini - Swastani Zai, Leo; Laoli, Meniria; Marampa, Elieser R (PEADA': Jurnal Pendidikan Kristen, 2023)
The phenomenon of bullying is one of the problems that occur quite a lot. This problem has been considered a common problem in society and even schools. As a result, many are negatively affected by the phenomenon of bullying including early childhood. Therefore, this research focuses on one way to deal with early childhood bullying with the storytelling method using hand puppet media. The stories told are Bible stories full of noble Christian values. Using a qualitative method, the author collects scientific sources relevant to the research problem to be analyzed more deeply. The results showed that the storytelling method using hand puppet media is more effective for early childhood because they are very interested in the form of storytelling using media. The Bible stories that can be told include stories that are full of the value of loving each other (Genesis 37-42; Luke 10: 25-37; Matthew 5: 44-45), about the value of human beings who are very valuable because they are in the image and likeness of God (Genesis 1: 26), not hurting other people's feelings with dirty words (Ephesians 4: 29), not judging (Romans 2: 1), and finally emphasizing that hateful actions and feelings are very disliked by God (1 John 3: 15). Thus, the message conveyed in the story using hand puppet media can be more easily understood by children. This can also help children to understand the dangers of bullying so that it is hoped that children's character can be formed for the better by not applying bullying behavior in everyday life.  Keywords: bullying, hand puppet, PAK, storytelling method